A Demographic Approach to the Family Structure in Asia and Africa. (3rd July 2017) - Susuman, A. Sathiya; Lailulo, Yishak; Latief, Abduraghiem; Odimegwu, Clifford
ABSTRACT: Family demography is the study of family structure. Family formations have resemblance in Asia and Africa, for instance most of the marriages practices in these two countries have been of the form of arranged marriages. The objective of this study is to investigate the family structure between sub-Sahara Africa and Asian continents. Secondary information (data) from different literature reviews was used. The information will be qualitative investigations done during different years by different countries. The causes of child marriage in Africa are due to poverty, tradition, protecting family honor and gender inequalities. In South Asian countries the highest number of nuclear household families is found in India. Policymakers, researchers and government and non-governmental organizations will get a better understanding of family issues within the households of those countries.